Automatic scoping of task clauses for the OpenMP tasking model - Wang, Chun-Kun; Chen, Peng-Sheng (The Journal of supercomputing, 2015)
OpenMP provides an easy-to-learn and powerful programming environment for the development of parallel programs. We propose here an algorithm for the automatic correction of the OpenMP tasking model. Assuming a compiler or programmer has identified task regions in the source programs, the proposed algorithm will automatically generate correct task clauses and synchronization. The proposed algorithm is implemented here based on the ROSE compiler infrastructure; 14 benchmark programs are tested, each of which has had all clauses in the task directives removed for the evaluation. The results of this experimental evaluation show that the proposed technique can successfully generate correct clauses for the tested benchmark programs. The proposed technique can simplify the parallelizing of programs using the OpenMP tasking model, making parallel programming more effective and productive.